Local Public Financial Management - Shah, Anwar (Washington, DC: World Bank, 2012)
This volume provides an overview of local government financial accounting and reporting and where better practices in cash management are documented. The use of transparent procurement processes to mitigate corruption is also elaborated on while practical guidance is imparted on how and when to use debt, how to assess debt affordability, what debt to use, how to issue debt, and how to manage debt. The use of internal controls and audits to ensure efficiency and integrity is highlighted in this volume with particular emphasis on the role of external audit in combating corruption. Audit methods to detect corruption are also presented and discussed. The volume represents a collaborative effort of the Swedish International Development Cooperation Agency and the World Bank Institute to support reform of the public expenditure management and financial accountability systems in developing countries, especially in Africa.